Role of leucine-rich repeat kinase 2 in severe acute pancreatitis - Otsuka, Yasuo; Minaga, Kosuke; Kudo, Masatoshi; Watanabe, Tomohiro (Frontiers in Immunology, 2024)
Introduction: Intrapancreatic activation of trypsinogen caused by alcohol or high-fat intake and the subsequent autodigestion of the pancreas tissues by trypsin are indispensable events in the development of acute pancreatitis. In addition to this trypsin-centered paradigm, recent studies provide evidence that innate immune responses triggered by translocation of intestinal bacteria to the pancreas due to intestinal barrier dysfunction underlie the immunopathogenesis of acute pancreatitis. Although severe acute pancreatitis is often associated with pancreatic colonization by fungi, the molecular mechanisms linking fungus-induced immune responses to the development of severe acute pancreatitis are poorly understood. Leucine-rich repeat kinase 2 (LRRK2) is a multifunctional protein that mediates innate immune responses to fungi and bacteria. Mutations in Lrrk2 is a risk factor for Parkinson's disease and Crohn's disease, both of which are driven by innate immune responses to gut organisms. Discussion: In this Minireview article, we discuss how activation of LRRK2 by the recognition of fungi induces severe acute pancreatitis.